Telerehabilitation to Address the Rehabilitation Gap in Anterior Cruciate Ligament Care: Survey of Physical Therapists/Care Providers - Elizabeth C. Gardner; Corey Podbielski; Emma Dunphy (Telemedicine Reports)
Background: While the importance of structured rehabilitation following anterior cruciate ligament reconstruction (ACLR), particularly in the return-to-sport phase, is known, for most patients, supervised physical therapy is often completed before this time point. The recent emergence of telerehabilitation and other digital health interventions has the potential to address this “rehabilitation gap.” Methods: The study was conducted as a cross-section, online survey collecting qualitative and quantitative data from open and closed questions. Inclusion criteria included local qualified physical therapists or other professionals working with ACLR patients. Results: Eighty-three percent of respondents experienced a “rehabilitation gap” with their ACLR patients. Few reported currently utilizing apps or websites (9.74%). The majority (41/58) reported experience with telerehabilitation, and 84% felt that there was a role for digital rehabilitation strategies to address the “rehabilitation gap.” The vast majority (94.74%) of participants felt that standard commercial insurance did not permit sufficient rehabilitation. Discussion: While the majority of our respondents acknowledged the existence of a “rehabilitation gap,” as well as familiarity with and confidence in telerehabilitation, few were using this technique at the time of our survey. This suggests an opportunity for development in this space.